2009
DOI: 10.1016/s1472-6483(10)60033-8
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide regulates lipopolysaccharide-induced nitric oxide synthesis and tissue damage in the murine uterus

Abstract: In women, the association between chronic marijuana smoking and early miscarriage has long been known. Anandamide, a major endocannabinoid, mimics some of the psychotropic, hypnotic and analgesic effects of Delta(9)-tetrahydrocannabinol, the psychoactive component of marijuana. The uterus contains the highest concentrations of anandamide yet discovered in mammalian tissues and this suggests that it might play a role in reproduction. The production of small amounts of nitric oxide (NO) regulates various physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…We are the first group to show uterine NAPE-PLD changes in the last part of pregnancy in mice. Here we demonstrated that, as we have previously shown for early pregnancy stages (Vercelli et al 2009), LPS increases Nape-pld mRNA and protein expression in the uterus in the late stages of pregnancy. This finding correlates with Liu et al (2003), who have demonstrated that LPS increases NAPE-PLD activity and AEA levels in RAW264.7 mouse macrophages.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We are the first group to show uterine NAPE-PLD changes in the last part of pregnancy in mice. Here we demonstrated that, as we have previously shown for early pregnancy stages (Vercelli et al 2009), LPS increases Nape-pld mRNA and protein expression in the uterus in the late stages of pregnancy. This finding correlates with Liu et al (2003), who have demonstrated that LPS increases NAPE-PLD activity and AEA levels in RAW264.7 mouse macrophages.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have shown that LPS affects FAAH activity and/or expression. Indeed, incubation of uterine explants from mice in day 7 of pregnancy with LPS increases FAAH activity (Vercelli et al 2009), whereas in human peripheral lymphocytes, LPS downregulates FAAH expression and increases AEA levels (Maccarrone et al 2001). We were unable to detect any changes in FAAH activity in our model of LPSinduced preterm labor.…”
Section: Discussionmentioning
confidence: 71%
“…Since m-AEA was also capable of inducing NO production, we examined whether LPS-induced NO production was mediated by AEA. Our results showed that decidual and uterine LPS-induced NO production was abrogated by co-incubation with CB1 (AM251) antagonist, which suggests that AEA is mediating LPS effect [9,10] .…”
Section: Inflammatory Agents In Septic Miscarriagementioning
confidence: 57%
“…To confirm that AEA was modulating NO levels via iNOS, tissues were incubated in the presence of m-AEA plus 1,400 W (a selective iNOS inhibitor). We observed that NO production induced by m-AEA was markedly reduced by co-incubation of m-AEA with 1,400 W [9,10] . Since m-AEA was also capable of inducing NO production, we examined whether LPS-induced NO production was mediated by AEA.…”
Section: Inflammatory Agents In Septic Miscarriagementioning
confidence: 78%
“…In previous studies, although endocannabinoids have been reported to have the proinflammatory role in the development of inflammation under certain pathologic conditions (Vercelli et al, 2009;Gatta et al, 2012), numerous reports have shown that endocannabinoids exert anti-inflammatory action in a variety of experimental models of inflammatory disease, including experimental hepatitis (Hegde et al, 2008), inflammatory bowel disease (Di Sabatino et al, 2011), lipopolysaccharide (LPS)-induced pulmonary inflammation (Berdyshev et al, 1998), nephropathy (Mukhopadhyay et al, 2010a;Mukhopadhyay et al, 2010b), and multiple sclerosis (Mestre et al, 2005). Among endocannabinoids, anandamide (AEA) has been documented to exert anti-inflammatory effects, but it has also been considered as a source of proinflammatory factors (Gatta et al, 2012).…”
Section: Introductionmentioning
confidence: 97%